Reconstruction of Multiple Digital Defects by Temporary Syndactylization Using a Lateral Arm Free Flap - Ki, Sae Hwi; Yoon, Jin Myung; Park, Tae Jun; Choi, M. Seung Suk; Hong, Min Ki (Archives of Plastic Surgery, 2022)
Background Soft tissue defects of the multiple finger present challenges to reconstruction surgeons. Here, we introduce the use of a lateral arm free flap and syndactylization for the coverage of multiple finger soft tissue defects.Methods This retrospective study was conducted based on reviews of the medical records of 13 patients with multiple soft tissue defects of fingers (n = 33) that underwent temporary syndactylization with a microvascular lateral arm flap for temporary syndactylization from January 2010 to December 2020. Surgical and functional outcomes, times of flap division, complications, and demographic data were analyzed.Results Middle fingers were most frequently affected, followed by ring and index fingers. Mean patient age was 43.58 years. The 13 patients had suffered 10 traumas, 2 thermal burns, and 1 scar contracture. Release of temporary syndactyly was performed 3 to 9 weeks after syndactylization. All flaps survived, but partial necrosis occurred in one patient, who required a local transposition flap after syndactylization release. The mean follow-up was 15.8 months.Conclusion Coverage of multiple finger defects by temporary syndactylization using a free lateral arm flap with subsequent division offers an alternative treatment option.
Keywords: soft tissue defects; multiple defects; traumatic injury; amputation; free flap